Co lze »vyčíst z ruky« aneb somatické frazémy v proměnách času - Pacovská, Jasňa; Lábus, Václav; Škodová, Svatava (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The paper deals with somatic idioms based on Czech lexeme ruka (hand). For the analysis a collocation v rukou (i.e. in hands) was chosen. Analyzed data come especially from Czech Radio news 1977 and 1997 (from a demo version of the platform being developed for automatic transcription and sophisticated access to historical audio archive of the Czech Radio), and from the Czech National Corpora. The analysis should demonstrate a ratio between basic and figurative meaning of the chosen collocation, its semantic profiles, and should reveal potential ideological implicit meaning.
Keywords: cognitive linguistics; somatic idioms; basic meaning; figurative meaning; ideology; news